2019
DOI: 10.3389/fphar.2019.01091
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dexmedetomidine Dose to Prevent Emergence Agitation Under Sevoflurane and Remifentanil Anesthesia During Pediatric Tonsillectomy and Adenoidectomy

Abstract: Background: Emergence agitation (EA) is a common pediatric complication after sevoflurane anesthesia that can be prevented with dexmedetomidine. However, an inappropriate dose of dexmedetomidine can cause prolonged sedation and cardiovascular complications. Thus, we evaluated the optimal dose (ED95) of dexmedetomidine for preventing EA with sevoflurane and remifentanil anesthesia after pediatric tonsillectomy and adenoidectomy. Methods: We enrolled American Society of Anesthesiologists (ASA) I and II children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…At present, there is no clear conclusion on the greatest dose of DEX for preventing EA in children. Zhang et al (96) revealed that intravenous DEX infusion at 0.30 μg/kg could prevent half of or all EA after general anesthesia during pediatric tonsillectomy and adenoidectomy. Manning et al (97) suggested that intravenous DEX 0.5 μg/kg could significantly reduce EA incidence in children with minimal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no clear conclusion on the greatest dose of DEX for preventing EA in children. Zhang et al (96) revealed that intravenous DEX infusion at 0.30 μg/kg could prevent half of or all EA after general anesthesia during pediatric tonsillectomy and adenoidectomy. Manning et al (97) suggested that intravenous DEX 0.5 μg/kg could significantly reduce EA incidence in children with minimal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, dexmedetomidine can improve the cognitive function in children during recovery from general anesthesia ( 96 ) and contributes to dose-dependent inhibition of EA or ED after medical procedures ( 97 ). The optimal dose (ED 95 ) of dexmedetomidine for preventing EA was 0.30 μg/kg (95% CI: 0.21–1.00 μg/kg) ( 83 ). An animal experiment demonstrated that dexmedetomidine could enhance spatial learning and memory in neonatal rats under physiological conditions through promoting hippocampal neurogenesis ( 98 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various doses of dexmedetomidine were shown to assist in the prevention of EA after sevoflurane-based anesthesia in pediatrics [25]. Supporting evidence suggested by Zhang Y-Z et al [26] that a dose of 0.3 μg/kg dexmedetomidine prevented 95% of sevoflurane-associated ED during pediatric tonsillectomy and adenoidectomy.…”
Section: Discussionmentioning
confidence: 77%